PENGARUH PEMBERIAN PUPUK KASCING DAN NPK MUTIARA 16:16:16 TERHADAP PERTUMBUHAN DAN HASIL OKRA (Abelmoschus esculentus (L.) Moenc.) SERTA BAWANG MERAH (Allium ascalonicum L.) DENGAN SISTEM TUMPANG SARI - Wahyu Hidayatullah; T. Rosmawaty; M. Nur (DINAMIKA PERTANIAN, 2020)
ABSTRACT The purpose of this study is to examine the interactions between kascing fertilizers and mutiara NPK 16:16:16 on the growth and production of okra and shallots in the intercropping system. This research used a completely randomized factorial design, consisting of two factors. The first factor was the application of vermicompost (K), consisting of 4 levels, namely 0, 750, 1500 and 2250 g/plot and the second factor was NPK 16:16: 16 (N), consisting of 4 levels, namely 0, 15, 30 and 45 g/plot, so that obtained 16 treatment combinations with 3 replications and 48 experimental units. Each unit consisted of 4 plants per plot and 2 plants are samples, so that the plant had 192 plants for okra plants and 5 plots for shallots and 2 plants was become samples with total plants of 240. Based on research results indicated that intercropping system on okra plants and shallots resulted smaller plant growth and production compared to monocultures. The interaction of kascing fertilizer and NPK 16:16:16 fertilizer had no significant on all observed parameters. The main effect of the dose of kascing fertilizer was a significance on all observed parameters. The best treatment was significant on a dose of kascing fertilizer of 2250 g/plot. The main effect of the 16:16:16 NPK dose was significant on all observed parameters. The best treatment was found on NPK 16:16:16 with dose of 45 g/plot. Keywords: Kascing, Mutiara 16:16:16, Okra, Onion